2014
DOI: 10.1002/asia.201402643
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Regioselective Addition of Nucleophilic Silicon Across Terminal and Internal Carbon–Carbon Triple Bonds

Abstract: The copper(I) alkoxide-catalyzed release of a silicon-based cuprate reagent from a silicon-boron pronucleophile is applied to the addition across carbon-carbon triple bonds. Commercially available CuBr⋅Me2S was found to be a general precatalyst that secures high regiocontrol for both aryl- and alkyl-substituted terminal as well as internal alkynes. The solvent greatly influences the regioisomeric ratio, favoring the linear regioisomer with terminal acceptors. This facile protocol even allows for the transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…This difference suggests that the nitrogen atom in 35 may coordinate to palladium, thereby facilitating the activation of the Si-B bond. Interestingly, these authors also found that Pd(OAc) 2 promotes b-elimination of 35 in the presence of styrene; the thus-formed silene led to the formation of 1,3-disilacyclobutanes (35)(36)(37)Scheme 7,bottom).…”
Section: Functionalization Of Unsaturated Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…This difference suggests that the nitrogen atom in 35 may coordinate to palladium, thereby facilitating the activation of the Si-B bond. Interestingly, these authors also found that Pd(OAc) 2 promotes b-elimination of 35 in the presence of styrene; the thus-formed silene led to the formation of 1,3-disilacyclobutanes (35)(36)(37)Scheme 7,bottom).…”
Section: Functionalization Of Unsaturated Compoundsmentioning
confidence: 98%
“…At about the same time, a related regioselective protosilylation of terminal alkynes was presented by Oestreich and coworkers (34a, s-u, y -E-53a, s-u, y, Scheme 19). 35 Unlike the above reports about ligand-controlled regioselectivity, commercially available CuBrÁSMe 2 was used as a catalyst to reach high regioselectivity (up to 99 : 1) without any need for external ligands. Moreover, the solvent showed great influence on the regioisomeric ratio.…”
Section: Scheme 17mentioning
confidence: 99%
“…Oestreich et al performed hydrosilylations in good yield on terminal alkynes with a wide range of substituents, including alkyl-, silyl-, and electron poor and electron rich aryl substituents (Table , Method B) . These reactions also exhibited decent to high regioselectivity.…”
Section: Silylations Using Silylboranesmentioning
confidence: 99%
“…1 The concentration of the silyllithium solution was confirmed by titration according to the Gilman's method. 2 Silyl substituted products 3aa, 3 3ba, 3 3ca, 3 3da, 4 3ea, 5 3fa, 6 3ha, 6 3ia, 3 3ka 3 , 3la, 3ab, 7 3ac, 8 3ad, 9 3ad', 10 7, (Z)-and (E)-3ma 11,12 were identified by 1 H NMR and comparison of GC retention time with the authentic samples prepared according to the Experimental Procedures in SI or the reported procedures. Analyses of the silyl substitution reactions with substrates 1f, 1g, and 1j were carried out using GC-MS. NMR spectra were recorded on JEOL JNM-ECX400P and ECS-400 spectrometer ( 1 H: 400 MHz and 13 C: 100 MHz).…”
Section: General and Materialsmentioning
confidence: 99%